Predictive value of HDL cholesterol for cancer‐associated venous thromboembolism during chemotherapy. (17th October 2014) - Ferroni, P.; Roselli, M.; Riondino, S.; Guadagni, F.
Summary Background Dyslipidemia is a well‐known risk factor for the development of atherothrombosis; however, its involvement in venous thromboembolism (VTE) is still debated. Low levels of HDL cholesterol (HDL‐C) have been found to be associated with VTE, which is a common complication of cancer and its treatment. VTE incidence is increased in cancer patients, especially those undergoing chemotherapy. Objective We sought to investigate the value of pretreatment HDL‐C in the risk prediction of future VTE in a population of ambulatory cancer patients undergoing chemotherapy. Patients and Methods Blood lipid composition was retrospectively evaluated in 592 consecutive patients with primary (n = 373) or relapsing/recurrent (n = 219) solid cancers at the start of a new chemotherapy regimen (12% neoadjuvant, 31% adjuvant, 57% metastatic). Results VTE occurred during chemotherapy in 38 patients (median time‐to‐event: 3 months). Mean HDL‐C levels were lower in patients who developed VTE during chemotherapy (41 mg dL−1; standard deviation [SD] 13 mg dL−1) than in those who did not (48 mg dL−1; SD 14 mg dL−1). Cox proportional hazard survival analysis showed that HDL‐C levels ≤ 43 mg dL−1 were able to significantly predict a first VTE episode, with a hazard ratio of 2.87 (95% confidence interval 1.45–5.68). Moreover, patients with HDL‐C levels ≤ 43 mg dL−1 had worse 1‐year VTE‐free survival (86%) than those with HDL‐C levels > 43 mg dL−1 (96%; log rank test, 3.14). Conclusions Patients with low HDL‐C levels have a three‐fold higher risk of developing a first VTE episode during chemotherapy. Baseline analysis of HDL‐C levels might be of clinical value in predicting VTE in cancer outpatients treated with anticancer drugs.